PEMANFAATAN MEDIA CERITA BERGAMBAR DALAM MANAJEMEN KREATIVITAS ANAK - Rozi, Fathor; Darmanti , Hanifah (Universitas Nurul Jadid, 2022)
The purpose of the study referred to here is to describe how children's creativity management through the medium of illustrated stories in family planning. az-Zainiyah Karanganyar Paiton Probolinggo. In order to obtain data from the results of research, conducted research is a qualitative type with case studies as the approach. Data collection techniques with participant observation, in-depth interviews and documentation analysis. Meanwhile, the data analysis technique uses the Miles Huberman model. The results of field research obtained findings that the learning process in the management of children's creativity through the medium of illustrated stories in family planning. az-Zainiyah Karanganyar Paiton Probolinggo through planning, implementing and evaluating learning. The implication is that educators must carry out careful learning planning so that children's creativity increases optimally.